An Argumentative Perspective to Conflictive Interpretation of Knowledge - Martínez, Diego César (2021)
In many scenarios, a set of beliefs can be interpreted in different ways, leading to different outcomes. In this work we propose an argumentation-based view of the interpretation of pieces of knowledge, using legal provisions as a leading example. We formalize conflicts and entailment towards a Characterization of an acceptable, rational position of the agent on a set of knowledge, i.e. a subset of interpretations, inspired by argumentation semantics.